THE IMPACT OF CHANGE MANAGEMENT ON THE IMPLEMENTATION OF ORGANISATIONAL STRATEGY: A CASE STUDY OF NATIONAL HOME BUILDERS REGISTRATION COUNCIL (Singaporean Journal of Business Economics and Management, 2016)
Organisations are changing their strategies in order to improve their operations. National Home Builders Registration Council (NHBRC) has grown over the years, and this has led to it continuously changing in order to meet organisational goals and objectives. The aim of the study was to assess the impact of change management on the implementation of NHBRC's organisational strategy. A quantitative research method was used for the study. Further, a survey instrument was used to collect data from the following three levels of employees: executives, senior management and general employees within NHBRC. The data was collected from 70 participants, using non-probability (quota) sampling.